Effect of Carrot Powder on Quality of Multipurpose Flour based Snack Food - Patel, Krishna Kumar; Liaquati, S. A.; Khan, M. A.; Minz, P. S. (Journal of Agricultural Engineering, 2014)
Different combinations of multipurpose flour (flour of rice, wheat and Bengal gram) and three levels of carrot powder (2.5, 5 and 7.5 %) were used for the preparation of fried snack food (sev). The physico-chemical and sensory quality of snack food was evaluated. The fat content ranged between 24 – 35%, moisture content 1.0 – 2.2%, TBA 0.065 – 0.085, FFA 0.26 –0.34%, PV 3.25 – 4.30, pH 7.2 –7.6, hardness 13.32 to 28.92N, while log cfu.g-1 (total plate count) was non-detectable. The prediction equations were also developed.